Effects of probiotics on liver function, inflammation, and gut microbiota in alcoholic liver injury: a systematic review and meta-analysis - Saadh, Mohamed J.; Sabah Ghnim, Zahraa; Salih Mahdi, Morug; Arora, Vimal; Rekha, M. M.; Sharma, Ashish; Juneja, Bhanu; Aminov, Zafar; Mohammed Taher, Waam; Alwan, Mariem; Jasem Jawad, Mahmood; Khdyair Hamad, Atheer (Frontiers in Nutrition, 2025)
PurposeThis systematic review and meta-analysis aimed to evaluate the effects of probiotic supplementation on alcohol metabolism, liver function biomarkers, inflammatory indicators, and gut microbiota composition in patients with alcoholic liver disease (ALD), providing insights into their potential therapeutic role.MethodsA comprehensive search of the PubMed, Scopus, Web of Science, and Cochrane Library databases identified clinical studies assessing probiotic interventions in adults with ALD.ResultsA total of 12 clinical trials conducted between 2008 and 2025 were included. Probiotic supplementation resulted in significant reductions in liver enzymes, including ALT (WMD = −10.10; 95% CI: −15.34, −4.87) and AST (WMD = −13.05; 95% CI: −21.33, −4.78). No significant effects were observed for GGT or ALP. Probiotics did not significantly influence blood alcohol or acetaldehyde levels. Regarding inflammatory markers, probiotics did not significantly affect LPS, TNF-α, IL-1β, or IL-6, and IL-10. Microbial analyses showed an increase in beneficial gut bacteria, including Lactobacillus, Bifidobacterium, Faecalibacterium, and Prevotella, and a decrease in pathogenic taxa such as Escherichia and Shigella.ConclusionProbiotic supplementation shows promising benefits for improving liver enzyme profiles and modulating the gut microbiota in patients with ALD. However, inconsistent effects on markers of inflammation and alcohol metabolism highlight the need for large-scale, high-quality randomized trials to confirm the therapeutic potential of probiotics in ALD.